This virus of science fiction: Disease and otherness in the work of Caio Fernando Abreu - Magri, Milena Mulatti [UNESP] (FapUNIFESP (SciELO), 2018)
In this essay, we analyse how Caio Fernando Abreu's work represents AIDS during two distinct moments. The first moment is concerned with the appearance of the first cases of AIDS in Brazil. The second moment is concerned with the writer's diagnosis of the disease. AIDS is characterized, since its beginning, as a socially feared and stigmatized disease, which engendered the social exclusion of seropositive patients. The comparison of these two different moments allows us to observe a change in how Abreu's work understands the disease. The texts shift from a perception of the disease as strange and fearsome to a form of otherness that becomes an integral part of the self-subject.
Esse vírus de science fiction: Doença e alteridade em Caio Fernando Abreu
Keywords: AIDS; Caio fernando abreu; Otherness